Cognitive self-management requires the phenomenal registration of intrinsic state properties. - Peters, Frederic (Philosophical Studies, 2020)
Cognition is not, and could not possibly be, entirely representational in character. There is also a phenomenal form of cognitive expression that registers the intrinsic properties of mental states themselves. Arguments against the reality of this intrinsic phenomenal dimension to mental experience have focused either on its supposed impossibility (since the brain possesses no such properties), or secondly, the non-appearance of any such qualities to introspection. This paper argues to the contrary, that the registration of cognitive state properties does take place independently of representational content; and necessarily so, since it supports an independent function—self-management. Given the fact that unlike a computer, the brain must, of necessity, operate itself, it needs to be in touch with itself to do so. Intrinsic phenomenal forms of cognitive expression allow the brain to do just that by registering characteristics of the cognitive states themselves. Self-management might well prove to constitute the prime reason for the emergence of subjectivity itself.